2015
DOI: 10.1016/j.ntt.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury exposure during early Xenopus laevis development affects cell proliferation and death but not neural progenitor specification

Abstract: Methylmercury (MeHg) is a widespread environmental toxin that preferentially and adversely affects developing organisms. To investigate the impact of MeHg toxicity on the formation of the vertebrate nervous system at physiologically relevant concentrations, we designed a graded phenotype scale for evaluating Xenopus laevis embryos exposed to MeHg in solution. Embryos displayed a range of abnormalities in response to MeHg, particularly in brain development, which is influenced by both MeHg concentration and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
(66 reference statements)
3
11
0
Order By: Relevance
“…Thus, in addition to DNA fragmentation, this low concentration of MeHg showed a deleterious effect on gene replication. This hypothesis may be also supported by a recent study reporting alterations in gene expression during exposure to this heavy metal [ 29 ]. Still, the values of NBr/MNC and NBu/MNC ratios (0.91 and 1.75, respectively) point to the formation of nucleoplasmic bridges as the main process responsible for the presence of micronuclei.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, in addition to DNA fragmentation, this low concentration of MeHg showed a deleterious effect on gene replication. This hypothesis may be also supported by a recent study reporting alterations in gene expression during exposure to this heavy metal [ 29 ]. Still, the values of NBr/MNC and NBu/MNC ratios (0.91 and 1.75, respectively) point to the formation of nucleoplasmic bridges as the main process responsible for the presence of micronuclei.…”
Section: Discussionsupporting
confidence: 63%
“…Apoptotic cells were observed mainly in the mantle layer, the same layer where γ -H2A.X-positive cells were found. This combination of data reinforces the argument that the toxicity of MeHg seems to activate the signaling cascade of programmed cell death or apoptosis in both adult [ 44 46 ] and developing CNS [ 6 , 14 , 22 , 35 , 38 ]. Moreover, we proposed that the association between decreased proliferation and increased apoptosis may act as one cause of the reduction in the thickness of the spinal cord layers.…”
Section: Discussionsupporting
confidence: 82%
“…Neural cell proliferation was disturbed by MeHg, as demonstrated by in vitro and in vivo assays [ 14 , 35 , 36 ]. It was also demonstrated that MeHg affects the proliferation in all regions of the developing CNS, such as the spinal cord in Xenopus laevis and Danio rerio [ 37 , 38 ], as well as in the murine brain and cerebellum [ 34 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of methylmercury (MeHg) is a well-documented phenomenon; its effect on the developing central nervous system (CNS) has been investigated in humans since the 1970s, following environmental accidents [ 1 5 ]. Different experimental models, such as rats ( Rattus norvegicus ) [ 6 8 ], mice ( Mus musculus ) [ 9 11 ], chicks ( Gallus domesticus ) [ 12 , 13 ], fish ( Danio rerio ) [ 14 ], and amphibians ( Xenopus laevis ) [ 15 ] have also been used to investigate the cytotoxic effects of this organometal. Even at low concentrations MeHg causes cellular damage in the developing CNS that can lead to permanent impairment [ 16 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of developmental neurotoxicity generally use brain structures (brain, cerebellum, and hippocampus) as an organ model, given the well-documented behavioral (learning and memory deficit) and motor changes caused by MeHg poisoning [ 16 , 17 , 21 , 27 29 ]. However, the spinal cord is also an interesting model for neurodevelopmental toxicity studies because its structural organization is less complex than the encephalon and it has fewer tissue layers, allowing observation of the neurotoxic effects on cells at different stages of differentiation [ 14 , 15 , 30 ].…”
Section: Introductionmentioning
confidence: 99%